Halide Replacement with Complete Preservation of Crystal Lattice in Mixed‐Anion Lanthanide Oxyhalides. (3rd June 2021) - Udayakantha, Malsha; Handy, Joseph V.; Davidson, Rachel D.; Kaur, Jagjit; Villalpando, Graciela; Zuin, Lucia; Chakraborty, Sudip; Banerjee, Sarbajit
Abstract: A challenge in anion control in periodic solids is to preserve the crystal lattice while substituting for different anions of widely varying size and hardness. Post‐synthetic modification routes that place cations or anions in non‐equilibrium configurations are promising; however, such methods remain relatively unexplored for anion placement. Here, we report the synthesis of LaOI nanocrystals by a non‐hydrolytic sol‐gel condensation reaction and their transformation into LaOBr, LaOCl, and LaOF nanocrystals along hard–soft acid–base principles using post‐synthetic metathesis reactions with ammonium halides. Anion displacement proceeds along halide planes, preserving the tetragonal matlockite structure. Energy‐variant X‐ray excited optical luminesce signatures of alloyed Tb 3+ ‐ions is a sensitive quantum reporter of the preservation of the cation sublattice and hardening of the crystal structure upon anion replacement. Abstract : Topochemical halide ion replacement in lanthanide oxyiodide nanostructures proceeds with complete preservation of the tetragonal matlockite crystal structure along a gradient of increasing anion hardness. Reformation of the anion lattice around the intact cation slabs impedes 5 D3 ‐ 5 D4 phonon‐assisted cross relaxation and is observed as a distinctive blue hue for an embedded quantum reporter.